Economics 2.0 : what the best minds in economics can teach you about business and life - Haring, Norbert; Storbeck, Olaf (New York, NY : Palgrave MacMillan, 2009)
Economists can help shape monetary policy, global policy and even how much you pay for a new pair of shoes. For example, do you know who benefits the most from globalization? How do fitness studios and providers of Internet access earn most of their money?: from the laziness and irrationality of their customers. This book features contributions from top thinkers in the economic field from around the world, such as Philippe Aghion, Paul Krugman, Daniel Gros, and George Lowenstein. It also includes chapters on: Financial Markets: Are They Completely Efficient or Totally Nuts (rational vs. emotional), and The Art of Selling: How marketers use consumer decision making data to sell us products we don't need. This text makes an impressive case for the argument that economics is not a dry science and that economics principles impact much of our day to day life. Completely without formulas and theoretical ballast, the authors present current findings of prominent economists and expand the economic knowledge of their readers. They manage to make complex relationships clear.
Includes bibliographical references and index
Keywords: Economics -- Psychological aspects